2007
DOI: 10.2337/dc07-0186
|View full text |Cite
|
Sign up to set email alerts
|

All-Cause Mortality Associated With Specific Combinations of the Metabolic Syndrome According to Recent Definitions

Abstract: OBJECTIVE -The aim was to evaluate the impact of specific component combinations of the metabolic syndrome on all-cause mortality risk in a large French cohort.RESEARCH DESIGN AND METHODS -The population was composed of 39,998 men (aged 52.6 Ϯ 8.3 years) and 20,756 women (aged 54.7 Ϯ 9.2 years) who were examined at the Investigations Préventives et Cliniques Center from 1999 to 2002. Mean follow-up was 3.57 Ϯ 1.12 years. Metabolic syndrome was defined according to three definitions: the National Cholesterol Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 35 publications
4
56
1
7
Order By: Relevance
“…It is important to stress that this association is not only related to higher blood pressure; the central obesity and increased fasting glucose levels were also independent traits consistently associated with arterial stiffness, whereas dyslipidemia was less so. These are the traits that are most often observed in a combination that is associated with the greatest mortality risk 61 . Apart from the induction of insulin resistance 62 , an increased influx of free fatty acids was proposed as a possible link between central obesity and PWV (ref.…”
Section: Metabolic Syndrome and Obesitymentioning
confidence: 99%
“…It is important to stress that this association is not only related to higher blood pressure; the central obesity and increased fasting glucose levels were also independent traits consistently associated with arterial stiffness, whereas dyslipidemia was less so. These are the traits that are most often observed in a combination that is associated with the greatest mortality risk 61 . Apart from the induction of insulin resistance 62 , an increased influx of free fatty acids was proposed as a possible link between central obesity and PWV (ref.…”
Section: Metabolic Syndrome and Obesitymentioning
confidence: 99%
“…It is important to stress that the association between (traits of) the metabolic syndrome and arterial stiffness is not only related to higher blood pressure; in addition to (and independently of) blood pressure, (central) obesity and increased fasting glucose levels were the traits consistently associated with arterial stiffness, whereas dyslipidaemia was less so. These are the three traits that are most often observed in combination, and this clustering is associated with the greatest mortality risk [88]. Analyses of the metabolic syndrome traits and their clustering expressed as a continuous score and the close examination of each trait (and/or combination of traits) in relation to increased arterial stiffness may therefore be a more appropriate approach in aetiological studies (for an example, see [84]).…”
Section: Estimates Of Arterial Stiffnessmentioning
confidence: 99%
“…Additionally, longitudinal studies have demonstrated variations in the risk of mortality according to the different combination patterns of metabolic syndrome components. 29,30 In our study, we observed that the most frequent We believe that our findings have a social impact because the study population was still undergoing the process of epidemiological transition, i.e. high rates of morbidity and mortality due to infectious and parasitic diseases 35 were observed to coexist with increased occurrence of non-communicable illnesses.…”
Section: Discussionmentioning
confidence: 57%